The Effect of Competency and Job Satisfaction On Performance Moderated By Commitment - Arie Jonatan Wirawan (CV. Publikasi Indonesia, 2023)
This research aims to analyze the influence of Competency and Job Satisfaction on Performance which is moderated by Commitment (Case Study at P.T. Garmindo Utama Jaya). The method in this research is quantitative which is used to research certain populations or samples through data collection using research instruments. In this research, the technique for collecting data sources was non-probability sampling using purposive sampling. The sample used was employees of PT Garmindo Utama Jaya who were collected via an online Google Form questionnaire totaling 150 respondents. This research uses Partial Least Squares SEM or what is called PLS-SEM. This research uses the Performance variable as the dependent (endogenous) variable, Competence and Job Satisfaction as the independent (exogenous) variable, and Commitment as the moderating variable. The results of this research show that there is a significant positive influence between the competency variables on performance, job satisfaction on performance, and commitment to performance. However, this research shows that the commitment variable is unable to moderate the relationship between competence and performance and the relationship between job satisfaction and performance. The limitation of this research is that it only examines the variables of competence, job satisfaction, commitment and performance with a sample of 150 people using a subjective assessment form. The theoretical implication of this research is that it can make this research a reference in the development of knowledge, especially in the field of management related to a company's performance, and can provide recommendations to companies to pay attention to variables that have a significant influence in carrying out their operational activities. The higher the level of competence, job satisfaction and commitment of an employee, the greater the performance, thereby increasing company profits.